Celebrating modern art : The Anderson Collection. - Auping, Michael; Benezra, Neal; Berkson, Bill; Boswell, Peter; Brenson, Michael; Brown, Julia; Cateforis, David; Clark, T.J.; Elderfield, John; Flam, Jack D.; Fletcher, Valerie J.; Garrels, Gary; et al. (Berkeley : University of California Press, 2000)
Adams, Phoebe ; Albers, Josef ; Alexander, Peter ; Allan, William ; Altoon, John ; Arneson, Robert ; Arnoldi, Charles ; Arp, Hans (Jean) ; Baizerman, Saul ; Bartlett, Jennifer ; Baziotes, William ; Beasley, Bruce ; Bell, Larry ; Benglis, Lynda ; Bengston, Billy Al ; Benton, Fletcher ; Berlant, Tony ; Berman, Wallace ; Bonnard, Pierre ; Borofsky, Jonathan ; Boucher, François ; Brancusi, Constantin ; Briggs, Ernest ; Brown, Christopher ; Brown, Kathan ; Burton, Scott ; Butterfield, Deborah ; Calder, Alexander ; Caro, Anthony ; Celmins, Vija ; Cézanne, Paul ; Close, Chuck ; Conner, Bruce ; Corbett, Edward ; Davis, Ronald ; DeFeo, Jay ; Degas, Edgar ; Delap, Tony ; Diebenkorn, Richard ; Dine, Jim ; Dove, Arthur ; Dubuffet, Jean ; Duchamp, Marcel ; Duff, John ; Ernst, Max ; Eversley, Frederick ; Feininger, Lyonel ; Fine, Charles ; de Forest, Roy ; Francis, Sam ; Frank, Mary ; Gabo, Naum ; Giacometti, Alberto ; Gilhooly, David ; González, Julio ; Gorky, Arshile ; Gottlieb, Adolph ; Graham, Robert ; Graves, Nancy ; Guston, Philip ; Gutkin, Peter ; Hartley, Marsden ; Hawkinson, Tim ; Held, Al ; Herriman, George ; Hockney, David ; Hofmann, Hans ; Holland, Tom ; Holub, Leo ; Hudson, Robert ; Hunt, Bryan ; Indiana, Robert ; Innerst, Mark ; Irwin, Robert ; Jacquette, Yvonne ; Jefferson, Jack ; Jensen, Bill ; Jess ; Johns, Jasper ; Judd, Donald ; Katz, Alex ; Kelly, Ellsworth ; Kline, Franz ; Kohn, Gabriel ; de Kooning, Willem ; Leger, Fernand ; Leonardo ; Lere, Mark ; Lethbridge, Julian ; Levine, Marilyn ; LeWitt, Sol ; Lichtenstein, Roy ; Lin, Maya ; Lipchitz, Jacques ; Lipton, Seymour ; Lobdell, Frank ; Louis, Morris ; Magritte, René ; Maillol, Aristide ; Marden, Brice ; Marin, John ; Martin, Agnes ; Mathieu, Georges ; Matisse, Henri ; May, Cliff ; McCracken, John ; etc.
geboorteplaats & -datum p. 352-392
Engels
Celebrating modern art : The Anderson Collection, San Francisco Museum of Modern Art, San Francisco, October 4, 2000 to January 15, 2001
boek